Daily field checking list by Walter Rosene, May 5, 1940 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene, Robert Walker and Otto D. Braker, May 5, 1940. Also notes a Blue Jay nest and an Eastern Phoebe nest each with eggs. In addition, they observed an Osprey eating a fish and two Willet's in flight. Plustek--flatbed